Seismic rehabilitation of gravity load-designed interior RC beam-column joints using ECC-infilled steel cylinder shell. (December 2021) - Qian, Huiya; Guo, Junchao; Yang, Xiuming; Lin, Feng
Abstract: A practical method was experimentally investigated to rehabilitate damaged gravity load-designed interior reinforced concrete beam-column joints featured with no transverse reinforcement. The method applied engineered cementitious composite (ECC) to fill a steel cylinder shell to encase the joint zone. Test program consisted of three as-built and two rehabilitated half-scale interior beam-column joint subassemblies subjected to cyclic loading with increasing amplitudes. The as-built specimens were first tested to shear failure of the joints and two of them were then rehabilitated in the joint zone using two cylinder shells of different dimensions for retesting. Test results found that the failure mode shifted from shear failure of the joints in the as-built specimens to flexural failure at the beam ends in the rehabilitated specimens. Peak values of column shear and corresponding deformability averaged an increase of about 32% and 60%, respectively. The beam-column joint using the cylinder shell of large dimension had a slightly better rehabilitation effect than that of small dimension. In addition, parametric studies were performed by means of the finite element method (FEM) based simulation. Numerical results indicated that appropriate thickness of the enlarged body of the cylinder shell ranged from 3 to 5 mm, and the proper length of the connection segment varied from 50 to 100 mm.